2023
DOI: 10.1111/eje.12894
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activities suspended: How the COVID‐19 affected the self‐confidence of Italian dental students

Abstract: IntroductionCOVID‐19 emergency caused several effects on the dental educational system, especially affecting courses including practical activities. The study aims to evaluate the impact of the suspension of dental clinical activities on the Italian dental students' self‐confidence. Furthermore, the other purpose of the research is to find an integrative didactics solution to improve the clinical training of dentistry during the COVID‐19 pandemic.Materials and MethodsA questionnaire was administered to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They felt self-motivated to make self-directed decisions and be prepared to take responsibility for their patients and self-learning. Francesca et al [ 18 ] also reported a positive impact on students with a shift toward productive learning strategies and increased engagement.…”
Section: Discussionmentioning
confidence: 99%
“…They felt self-motivated to make self-directed decisions and be prepared to take responsibility for their patients and self-learning. Francesca et al [ 18 ] also reported a positive impact on students with a shift toward productive learning strategies and increased engagement.…”
Section: Discussionmentioning
confidence: 99%